An Aramaic-Inscribed Lamatu Amulet from Zincirli - Degrado, Jessie (Bulletin of ASOR, 2017)
In the final volume of excavation reports from the Felix von Luschan expedition to Zincirli, Turkey, the editor, Walter Andrae, provided a brief iconographic description and an imperfect photograph of an Aramaic-inscribed Lamatu amulet from the site. The Old Aramaic inscription was, however, largely invisible in the photograph, and the epigraph went untranscribed and untranslated in this and all subsequent mentions. The present article represents a full edition and discussion of the amulet and its inscription on the basis of our examination of the object at the Vorderasiatisches Museum, Berlin. This artifact represents the only known instance of a local Aramaic script's use on an amulet dominated by Mesopotamian iconographic motifs, notably including Lamatu. It is an important witness to cultural contact and combination in an Aramaic/Neo-Hittite city-state of the 9th-8th centuries b.c.e. Due to the general paucity of Old Aramaic inscriptions, the epigraph also represents a significant addition to the broader extant corpus and contributes important data for understanding Old Aramaic palaeography, orthography, and onomastics.